Two-handed task performance in upper limb prosthesis users: rethinking measurement approaches. - Resnik, Linda; Borgia, Matthew; Heinemann, Allen W.; Stevens, Phillip; Ni, Pengsheng (Disability & Rehabilitation, 2025)
Purpose: The UEFS-P Two-Handed Task scale measures physical function of upper limb prosthesis users. Original scoring assumed a response of not performing a task indicated greater difficulty than the response, 'could not do' a task and collapsed several responses. This study explored alternative scoring approaches. Materials and Methods: Sample of 423 prosthesis users with major upper limb amputation. Scoring approaches included a partial credit model (PCM) of task difficulty rating, and six generalized linear mixed models accounting for number of tasks performed and task difficulty. Model fit and reliability were compared, and known group validity assessed. After selecting the best model, item fit, threshold and other parameters were evaluated. Concurrent validity with the original score was assessed. Results: The Poisson and PCM model was selected. Measures were significantly different by amputation level, had the largest F statistic, reliability was 0.78; Pearson correlation with original scoring was 0.82. Conclusion: The new scoring strategy addresses face validity and clinical relevance concerns. Including a count of tasks performed with a prosthesis is part of the latent construct of prosthesis task performance, adding information not considered in a PCM model. IMPLICATIONS FOR REHABILITATION: The UEFS-P Two-Handed Task scale is a patient-reported measure of function for upper limb prosthesis users in which the original scoring approach assumed that not performing a task indicated greater task difficulty and collapsed several response categories to improve structural validity of the measure. This study explored study alternative scoring approaches for the UEFS Two-handed Tasks scale and evaluate psychometric properties. The new scoring strategy proposed addresses concerns about face validity and clinical relevance of the original scoring approach, providing an updated method of assessing two-handed function in upper limb prosthesis users. The novel approach retains information about task performance and difficulty, and offers a new method of assessing two-handed task performance in upper limb prosthesis users